1982
DOI: 10.5962/bhl.title.47470
|View full text |Cite
|
Sign up to set email alerts
|

Empirical guidelines for use of irregular wave model to estimate nearshore wave height / by Michael G. Mattie.

Abstract: Irregular wave model Nearshore waves Wave heights 20. ABSTRACT (Xrorrtlaue on nv aide tf naceaoary and Identify by block number) An irregular wave technique based on a method developed by Goda (1975) and the SPM method for predicting nearshore wave height are compared with wave gage measurements from the CERC Field Research Facility. The SPM method is a classical monochromatic approach, while the irregular wave technique attempts to represent the actual distribution of ocean waves. These two techniques have ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Our results clearly indicate that the enzyme activation by the lipid is responsible for Ca 2÷ mobilization, as evidenced from the parallelism of the inhibition of both responses by several agents including PTX (a G-protein inhibitor), U73122 (a phospholipase C inhibitor) and PMA (an inhibitor for the receptormediated phospholipase C activation). In the previous study with Swiss 3T3 fibroblasts [5], the authors concluded that SIPinduced phospholipase C activation is not involved in Ca 2+ mobilization, although exogenous S1P induced both the enzyme activation and Ca 2+ mobilization. This conclusion was based on the observation that PMA treatment abolished SIPinduced activation of the enzyme but never affected the lipidinduced Ca -,+ mobilization [5].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Our results clearly indicate that the enzyme activation by the lipid is responsible for Ca 2÷ mobilization, as evidenced from the parallelism of the inhibition of both responses by several agents including PTX (a G-protein inhibitor), U73122 (a phospholipase C inhibitor) and PMA (an inhibitor for the receptormediated phospholipase C activation). In the previous study with Swiss 3T3 fibroblasts [5], the authors concluded that SIPinduced phospholipase C activation is not involved in Ca 2+ mobilization, although exogenous S1P induced both the enzyme activation and Ca 2+ mobilization. This conclusion was based on the observation that PMA treatment abolished SIPinduced activation of the enzyme but never affected the lipidinduced Ca -,+ mobilization [5].…”
Section: Discussionmentioning
confidence: 95%
“…with an increase in IP3 production probably reflecting the activation of phospholipase C, Ca 2÷ mobilization has been reported to be independent of the IP3 accumulation [5]. On the contrary, a very recent study with the same Swiss 3T3 fibroblasts showed that PTX treatment of the cells inhibited both SIP-induced phospholipase C activation and Ca 2÷ mobilization, suggesting an involvement of PTX-sensitive GTP-binding proteins in the SIP signaling [7].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…One particularly interesting sphingolipid metabolite, sphingosine-1-phosphate (S1P), a highly bioactive lipid, has been implicated in both extracellular and intracellular signalling processes (10). S1P acts as a second messenger participating in cellular signalling cascades that lead to cytoskeletal and motility changes, intracellular calcium signalling and protection from apoptosis (11)(12)(13)(14). We have previously developed an S1P-activating compound, K6PC-5, which showed an anti-ageing effect on both intrinsically and extrinsically aged skin (15).…”
Section: Introductionmentioning
confidence: 99%